Learning analytics tool for student performance - Teo, Andrew Shaoming (Nanyang Technological University, 2024)
This project presents the design and implementation of a Learning Analytics Tool designed to enhance the educational experience for secondary school students and teachers. This tool’s main objective is to provide insightful data visualizations of student performance, facilitate personalized learning experiences, and encourage active engagement in a student’s learning journey. The system features a user-friendly web application that supports features such as dashboard visualizations, adaptive quizzes, and sentiment analysis of discussion forums for students and teachers to interact with. Through a comprehensive system design and implementation process, the tool demonstrates the potential to bridge the gap in the utilization of learning analytics within secondary education, offering a potentially scalable solution to enhance learning outcomes in schools.